Are oxidative stress and ischemia significant causes of bladder damage leading to lower urinary tract dysfunction? Report from the ICI-RS 2019 - TARCAN, TUFAN (WILEY, 2020)
Several studies indicate that pelvic ischemia and oxidative stress may play a significant role in lower urinary tract dysfunction (LUTD), including detrusor overactivity (DO)/overactive bladder (OAB) and detrusor underactivity (DU)/underactive bladder (UAB). The present article addresses proposal 1: Are oxidative stress and ischemia significant causes of bladder damage leading to LUTD? from the 2019 International Consultation on Incontinence-Research Society (ICI-RS) meeting. Bladder ischemia in animals and humans is briefly described, along with the proposed progression from ischemia to LUTD. Bladder ischemia is compared with ischemia of other organs, and the ongoing development of pelvic ischemia animal models is discussed. In addition, the distribution of blood within the bladder during filling and voiding and the challenges of quantification of blood flow in vivo are described. Furthermore, oxidative stress, including potential biomarkers and treatments, and challenges regarding antioxidant therapy for the treatment of LUTD are discussed. Finally, seven critical research questions and proposed studies to answer those questions were identified as priorities that would lead to major advances in the understanding and treatment of lower urinary tract symptoms (LUTS)/LUTD associated with pelvic ischemia and oxidative stress.
Keywords: lower urinary tract symptoms; oxidative stress; pelvic ischemia; INCONTINENCE RESEARCH SOCIETY; BLOOD-FLOW; INTERNATIONAL CONSULTATION; NUCLEAR-DNA; MITOCHONDRIAL; ATHEROSCLEROSIS; SYMPTOMS; ASSOCIATION; RADIATION; SEVERITY